2001
DOI: 10.1159/000045992
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Circulating IgA Isolated from Patients with IgA Nephropathy on Superoxide and Fibronectin Production of Mesangial Cells

Abstract: Background: IgA nephropathy (IgAN) is characterized by predominant deposition of IgA in the glomerular mesangium. Serum IgA is often elevated in patients with IgAN, and it has been postulated that it is responsible for the mesangial lesions. However, the direct effect of circulating IgA on mesangial cells is not clear. Methods: We investigated the effects of sera and IgA which were isolated from patients with IgAN on thymidine uptake, superoxide and fibronectin production and fibronectin mRNA expression of cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Among this two, response to reactive oxygen species (ROS) attracted our attention. Studies have shown that high levels of oxidative stress exist in both plasma 19 , 20 and renal tissue especially mesangial cells 21 , 22 of IgAN patients. Our GSEA analysis suggested a decreased reflection to oxidative stress and antioxidant capacity in the transcriptome of patients.…”
Section: Resultsmentioning
confidence: 99%
“…Among this two, response to reactive oxygen species (ROS) attracted our attention. Studies have shown that high levels of oxidative stress exist in both plasma 19 , 20 and renal tissue especially mesangial cells 21 , 22 of IgAN patients. Our GSEA analysis suggested a decreased reflection to oxidative stress and antioxidant capacity in the transcriptome of patients.…”
Section: Resultsmentioning
confidence: 99%
“…The tracer used was alkaline phosphatase‐labelled human fibronectin. Samples were analysed with a spectrophotometer at 403 nm 10 …”
Section: Methodsmentioning
confidence: 99%
“…The activation of intracellular signaling mostly results in oxidative stress, as detected in mesangial cells cultured with aberrantly glycosylated IgA or IgA aggregates [7,8] and in renal biopsies of patients with IgAN, similar to what has been detected in diabetic nephropathy [9]. Signs of altered oxidation/antioxidation balance have been detected in sera and/or in erythrocytes of patients with IgAN, including increased levels of lipoperoxide or malondialdehyde and reduced activity of superoxide dismutase, catalase and glutathione peroxidase [10,11].…”
Section: Activation Of the Oxidative Stress Pathway In Iganmentioning
confidence: 99%